Influence of nitrogen on weed growth and competition with grain sorghum - Unruh, Bryan Jacob (Kansas State University, 2012)
Nitrogen (N) fertilizer intended for the crop may benefit highly competitive weeds to the detriment of the crop. A field experiment was conducted in 2009 to determine the influence of increasing N fertilizer rates and increasing Palmer amaranth densities on weed biomass and grain sorghum biomass and yield. Three rates were 0, 67, and 134 kg N ha-1 and natural populations of Palmer amaranth were thinned to densities of 0, 0.5, 1, 2, 4, and 8 plants m-1 of row. Palmer amaranth biomass increased as weed density and N rates increased. Weed-free grain sorghum yields were similar across all three N rates, and parameter estimates of yield across Palmer amaranth densities were not different between N rates. Based on the parameter estimates from the rectangular hyperbola model, initial slope (I) as density approached zero was 16%. Maximum expected yield loss (A) at high Palmer amaranth densities was 68%. Palmer amaranth showed a high response to N and the higher N rate increased the ability of the weed to reduce grain sorghum yield. A greenhouse experiment was conducted to determine the influence of six N rates on growth of six selected plant species, including grain sorghum, soybean, yellow foxtail, velvetleaf, Palmer amaranth and shattercane. Covariance analysis was performed with N rate as a covariate. Biomass of all species increased as N rate increased in both runs of the study. Soybean responded the least to N rate of all species in regards to biomass, height and leaf area production. In the first run, the biomass of three grass species (grain sorghum, yellow foxtail, shattercane) had similar estimates of slope and intercept of biomass across N rates. In the second run, the biomass slopes of grain sorghum and shattercane differed from soybean and were the only slopes that differed between species. Palmer amaranth had the highest rate of response as N increased but slopes of height were similar for Palmer amaranth, grain sorghum and shattercane. Soybean leaf area slopes were different from grain sorghum, yellow foxtail, and velvetleaf, but all other slopes were not different among species. Addition of N to grain sorghum increased weed growth and resulted in more yield loss as a result of weed density. The greenhouse study demonstrated that grain sorghum and Palmer amaranth increased in response similarly to the addition of N. Alternative N fertilizer management could play a role in minimizing Palmer amaranth impacts in grain sorghum production.
Keywords: Grain sorghum; Palmer amaranth; Nitrogen; Competition; Agriculture, General (0473); Agronomy (0285)